PENGARUH PROFITABILITAS, LIKUIDITAS, GROWTH POTENTIAL, DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN DIVIDEN - Arifin, Samsul; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to examine the influence of profitability, liquidity, growth potential, and managerial ownership to the dividend policy. The population is the companies which are engaged in the field of manufacturing industries which are listed in Indonesia Stock Exchange (IDX). The sample collection technique has been done by using purposive sampling and 11 companies which meet the criteria of manufacturing industries which are listed in Indonesia Stock Exchange in 2010-2013 periods have been selected as samples. The source of data of this research has been obtained from the Indonesia Stock Exchange (IDX), www.idx.co.id, Indonesian Capital Market Directory (ICMD), and the STIESIA Stock Exchange Corner (Indonesia School of Economic Surabaya). The hypothesis test has been done by using the multiple regressions equation analysis technique. The results of this study show that: (1) profitability and liquidity does not have any significant influence to the dividend policy, (2) growth potential has negative and significant influence to the dividend policy, and (3) managerial ownership has positive influence to the divident policy.Keywords: Profitability, Liquidity, Growth Potential, Managerial Ownership, and Dividend Policy.